Do Infants Less than 12 Months of Age with an Apparent Life-Threatening Event Need Transport to a Pediatric Critical Care Center?. (1st July 2013) - Kaji, Amy H.; Santillanes, Genevieve; Claudius, Ilene; Mittal, Manoj K.; Hayes, Katie; Lee, Jumie; Gausche-Hill, Marianne
Abstract Background. Some emergency medical services (EMS) systems transport infants with an apparent life-threatening event (ALTE) directly to hospitals capable of pediatric critical care (PCC) monitoring. Objective. To describe factors identifiable by EMS providers that distinguish ALTE patients who may require PCC monitoring and management. Methods. This was an observational analysis of ALTE patients who were transported by EMS and presented to four emergency departments (EDs). ED data were prospectively collected. Hospital records or reports from contacted parents were reviewed for interventions that mandated PCC management. We defined a priori the criteria by which PCC monitoring and management were required: if the subject needed 1) airway intervention with bag–valve–mask ventilation or advanced airway (e.g., endotracheal intubation) in the field, ED, or pediatric intensive care unit (PICU); 2) administration of vasopressors; 3) invasive monitoring; 4) surgery during the hospitalization; or 5) subspecialty consultation. Univariate analysis was performed to describe factors associated with requiring PCC management, and a multivariable model, accounting for within-hospital correlations, was developed. Results. A total of 513 patients were enrolled. Of these, 51 (9.9%) had an intervention warranting PCC management. Univariate predictors for requiring PCC management included prematurity, past medical history, resuscitation attempt, upper respiratory infection, apnea, previous ALTE, more than one ALTE in 24 hours, and cyanosis. The multivariable model yielded the following independent predictors for requiring PCC management: resuscitation attempt before EMS arrival, cyanosis, and more than one ALTE in 24 hours. This model demonstrated a sensitivity of 96.3%, a specificity of 25.8%, a negative predictive value of 98.3%, and a positive predictive value of 13.5%. Conclusion. Only 9.9% of infants presenting in the field with ALTE had an intervention warranting PCC management, suggesting that many ALTE patients may be safely transported to hospitals without PCC capability. This would allow for better resource utilization of specialty care hospitals and still provide an option for secondary transports for those few patients not correctly identified in the field as requiring PCC. History of resuscitation attempt, cyanosis, and more than one ALTE in 24 hours are independent risk factors for requiring PCC management. Key words: ALTE; apparent life-threatening event; transport decision; pediatric critical care; infants